2016
DOI: 10.17503/agrivita.v38i1.494
|View full text |Cite
|
Sign up to set email alerts
|

Yield Performance and Adaptation of Promising Amphibious Red Rice Lines on Six Growing Environments in Lombok, Indonesia

Abstract: The objectives of this study were to examine yield performance of promising amphibious red rice lines, and to evaluate their adaptability to six growing environments in Lombok, Indonesia. Ten promising amphibious red rice lines were tested together with their three parents and one national cultivar (Aek Sibundong), during the rainy extended to dry season 2014 (JanuaryJune 2014). The ten promising lines were obtained from two population sources, while the three parents were AKBC52, AKBC86, and a local cultivar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Among those promising lines, G21 produced the highest yield. Previous studies also confirmed that the highest yield was also in the G21 line, which is the AM10 amphibious red rice line [10], which also reported to show the highest grain yield in irrigated paddy system, whose treatment code was G10(F2BC4A52-42), which had average yield of 7.8 tons/ha [11].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Among those promising lines, G21 produced the highest yield. Previous studies also confirmed that the highest yield was also in the G21 line, which is the AM10 amphibious red rice line [10], which also reported to show the highest grain yield in irrigated paddy system, whose treatment code was G10(F2BC4A52-42), which had average yield of 7.8 tons/ha [11].…”
Section: Resultsmentioning
confidence: 57%
“…The main plot factor was red rice line comprising four genotypes (G04, G10, G15 and G21) while the subplot factor was intercropping comprising two treatments (T0= monocropped rice, T1= rice-peanut intercropping). Among the four red rice promising lines tested, two were upland rice lines (G04 and G10), and two lines (G15 and G21) were amphibious red rice lines resulted from previous research [11].…”
Section: Design Of the Experimentsmentioning
confidence: 99%
“…Formation of raised-beds, planting of pre-germinated red rice seeds, fertilizer application, mycorrhiza application, application of irrigation water, and harvest of the red rice were done exactly the same as those explained in Wangiyana et al [13], except for the dose of Phonska (NPK 15-15-15) fertilizer, which was full doses in this experiment. The red rice genotypes used were also the same as those explained in Wangiyana et al [13], which were previously selected from 11 promising lines of upland red rice genotypes and 12 promising lines of amphibious red rice genotypes [14]. The other difference was that there was an intercropping treatment in this experiment, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For this experiment, each pot was filled with 7 kg air-dried soil that has been sieved with 2 mm opening sieve, and watered up to the field capacity. The red rice genotype used in this study was the promising amphibious red rice line "F2BC4A86-3" (or "AM-G4") selected from results of a previous research [2]. For planting the red rice, seeding the pre-germinated AM-G4 seeds was done in a seedling tray filled with a mixture of soil and rice husk ash (1:1), which was thinned after one week to allow only two seedlings to grow per hole of the seedling tray.…”
Section: Implementation Of the Experimentsmentioning
confidence: 99%
“…Over the past few years, the need for red rice has continued to increase in accordance with the increasing people's awareness on the importance of health and recognition of the health benefit from consuming red rice instead of white rice. However, most of the existing red rice varieties are upland rice varieties, which are generally low in their average productivity [2]. Therefore, it is necessary to increase the productivity of red rice through application more productive rice cultivation technologies, one of which is by growing red rice under aerobic irrigation techniques, which was called as aerobic rice systems (ARS) [3].…”
Section: Introductionmentioning
confidence: 99%